The Poverty of Melania the Younger and Pinianus - Dunn, Geoffrey D. (Augustinianum, 2014)
Two literary sources, Palladius’ Historia Lausiaca and Gerontius’ Vita Melaniae, provide information about the ascetical activity of Melania the Younger and her husband Pinianus, two extremely wealthy aristocratic Romans in late antiquity. Peter Brown recently has sug-gested that they are to be seen as heroic individuals who embraced total renunciation of their possessions in contrast with the practice of regular expiatory almsgiving as recommended by Augustine of Hippo. This paper argues that while the generosity of their alms-giving was enormous and while Gerontius’ rhetorical objective was to portray them as engaging in total renunciation of riches, a careful reading of the texts reveals that much of their almsgiving came from their annual income and the sale or donation of some of their possessions, but that their income-generating capital investment in fixed assets like property was preserved, which enabled them to engage in acts of charity over a lengthy period of time. The only exception to this was their dispossession of property in Rome threat-ened by the presence of Alaric between 408 and 411 and other property in Spain and Gaul. Despite Melania’s preference for celi-bacy, frugal living and almsgiving, she and her husband remained wealthy individuals. Even their experiences in Africa, where Pinianus was nearly forced to become a presbyter in Hippo, much to Augustine’s embarrassment, indicates that they remained people of substance whose impressive and continual record of almsgiving gave them an authority in the local church that rivalled Augustine’s.